2011
DOI: 10.1051/0004-6361/201116798
|View full text |Cite
|
Sign up to set email alerts
|

The binary Be starδScorpii at high spectral and spatial resolution

Abstract: Context. Classical Be stars are hot non-supergiant stars surrounded by a gaseous circumstellar disk that is responsible for the observed IR-excess and emission lines. The influence of binarity on these phenomena remains controversial. Aims. δ Sco is a binary system whose primary suddenly began to exhibit the Be phenomenon at the last periastron in 2000. We want to constrain the geometry and kinematics of its circumstellar environment. Methods. We observed the star between 2007 and 2010 using spectrally-resolve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
72
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 33 publications
12
72
4
Order By: Relevance
“…We note that during 2009, when the redshifted portions of the rotating disk were beginning to occult the blueshifted side of the F star, three of four profiles show V <1 for λ < λ o , with λ o the central wavelength of the line, suggesting that photons from the F star are being scattered by extended hydrogen associated with disk material -which mainly covers the blueshifted hemisphere of the F star during ingress (2009). Phase shifts in three of the four spectra are positive, implying a source offset (Bonneau et al 2011a;Meilland et al 2011) to the south of the F star photocentre, which is consistent with the disk's orbital plane offset as defined by the interferometric imaging. The visibility in the Si II line shows some differential signal with respect to the continuum during 2009, but the amplitudes are minimal, with a small amount of blueshift relative to the line core.…”
Section: Qualitative Behavior Of the Differential Visibilitiessupporting
confidence: 67%
See 1 more Smart Citation
“…We note that during 2009, when the redshifted portions of the rotating disk were beginning to occult the blueshifted side of the F star, three of four profiles show V <1 for λ < λ o , with λ o the central wavelength of the line, suggesting that photons from the F star are being scattered by extended hydrogen associated with disk material -which mainly covers the blueshifted hemisphere of the F star during ingress (2009). Phase shifts in three of the four spectra are positive, implying a source offset (Bonneau et al 2011a;Meilland et al 2011) to the south of the F star photocentre, which is consistent with the disk's orbital plane offset as defined by the interferometric imaging. The visibility in the Si II line shows some differential signal with respect to the continuum during 2009, but the amplitudes are minimal, with a small amount of blueshift relative to the line core.…”
Section: Qualitative Behavior Of the Differential Visibilitiessupporting
confidence: 67%
“…This gaussian function is used to extract the minimum value of the visibility and the associated radial velocity and to estimate the full width at half maximum (in radial velocity) of the visibility drop. All the differential phase measurements have been oriented in the same way, which means that a positive offset represents an astrometric displacement towards the south in our case (Bonneau et al 2011a;Meilland et al 2011). The uncertainties of the differential interferometric quantities are obtained from a pure photon noise analysis.…”
Section: Obtaining the Differential Quantitiesmentioning
confidence: 99%
“…It is interesting to speculate that the periastron passage in 2000 contributed to the observed brightening. The secondary companion has a very eccentric orbit with a period of about 11 yr (for recent calculations see Tango et al 2009;Tycner et al 2011;Meilland et al 2011) and the periastron passage of its companion in 2011 offered an opportunity to study this system. We collected V-and B-band photometry for the 2009, In this work we use our V and B photometry to probe the innermost regions of the disk of δ Sco in order to determine the mass-loss rate and investigate the variability of these outbursts for this system.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent analyses of δ Sco orbit was done by Tycner et al (2011) using 96 measurements from the Navy Prototype Optical Interferometer (NPOI). Finally, Meilland et al (2011) have obtained new VLTI/AMBER and CHARA/VEGA data and conclude that the next periastron passage should take place around July 5, 2011 (± 4 days). They also found that the rotation appears to be Keplerian, with an inner boundary (photosphere/disk interface) rotating at the critical velocity.…”
Section: δ Scomentioning
confidence: 97%